Optimizing The Empowerment of Rukun Tetangga (RT) and Rukun Warga (RW) to Strengthen Community Participation in Early Detection Radicalism, Extremism, and Terrorism - Mochammad Ferdion Firdaus; Hikmat Zakky Almubaraq (Jurnal Manajemen Pelayanan Publik, 2022)
Early detection of radicalism, extremism, and terrorism is still not optimal. The reason is because of the limitations of the task force and prevention forums in involving the community. Several studies show that community participation is needed in the early detection. Strengthening community participation will be better by empowering organizations that are close to the community such as RT and RW. Therefore, this paper discusses the role of RT and RW in the early detection of radicalism, extremism, and terrorism including identifying the efforts that need to be made to optimize them. The method applied in this paper is library research with data and information sources from several books, journals, documentation, and legal products. The author analyzes data and information by reducing data, classifying data and processing data qualitatively. The results of the study show that RT and RW have an important role in the early detection of radicalism, extremism, and terrorism. Optimizing the empowerment of RT and RW in increasing early detection of radicalism, extremism, and terrorism is much more effective and efficient than prevention forums or task forces which are all temporary. Optimization of empowerment is achieved by improving the quality of several factors which include facilities and infrastructure, budget, human resources, and more productive work mechanisms.